Clinical Profile of COVID-19 Patients from March 2020 to March 2021 in Abepura Regional General Hospital (RSUD Abepura), Papua - Yenny Belinda Jioe; Helena Pakiding; Nancye Lorein; Dessy Yuliana; Febrianti Manga Mangontan; Fergina Stefany Berhitu (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: SARS-COV-2 infection has widely spread and caused high morbidity and mortality rates. Despite more than one year of the COVID-19 pandemic in Indonesia, there is no scientific report regarding COVID-19 from Papua. This study aims to assess the clinical profile of COVID-19 patients in Abepura Regional General Hospital (RSUD Abepura), Papua.Methods: We retrospectively recorded patients' age, sex, race, comorbidities, admitting and principal diagnoses, length of stay (LOS), and outcome (deceased/discharged) from the medical records from March 2020 to March 2021. Categorical data were described in frequencies and percentage, while numerical data were described in mean±SD or median and IQR. We analyzed the association between independent variables (age, sex, race, comorbidities, and diagnoses) with LOS and mortality rate.Results: We included 461 patients (58.6% female) with a median age of 36.90 (26.35-49.35) years who were hospitalized for 17 (12-25) days, in which 5.4% mortality occurred. Overall COVID-19 patients were dominated by non-Papuan race (75%). The most frequent comorbidities were hypertension (19.1%), electrolyte imbalance (10.2%), and diabetes (10.0%). Increased mortality rates were significantly associated with older age (≥65 years), cerebrovascular conditions, hypertension, coronary heart disease, liver disease, diabetes, and electrolyte imbalance (P<0.05). Moreover, several comorbidities, such as hypertension, coronary heart disease, diabetes and electrolyte imbalance, and a principal diagnosis of critical COVID-19, were associated with a significantly shorter period of LOS (P<0.05).Conclusion: Mortality and LOS due to COVID-19 in RSUD Abepura, Papua, are influenced by older age and several comorbidities.